A retrospective analysis of factors associated with selection of end-of-life care and actual place of death for patients with cancer. Issue 5 (2nd May 2014) - Kondo, Shunsuke; Shimazu, Taichi; Morizane, Chigusa; Hosoi, Hiroko; Okusaka, Takuji; Ueno, Hideki
Abstract : Objectives: The factors associated with end-of-life (EOL) care that patients with cancer selected and actual place of death (POD) is less elucidated. We analysed how specific EOL care, especially anticancer therapies, selected by patients with pancreatic carcinoma affected their POD in Japan. Setting: A retrospective cohort study using clinical records of a single institute. Participants: This study included 433 advanced or recurrent patients with pancreatic carcinoma who had completed standard chemotherapies and were receiving hospice care in the National Cancer Center Hospital between April 2008 and April 2011. Outcome measures: We analysed statistical association factors, demographic information, geographical differences, medical environment, EOL care selection, along with actual POD using logistic regression analysis. Results: Of the 433 patients, 147 selected palliative care units (PCUs) as the POD; 229, hospital; and 57, home with hospice care. POD selection was associated with several factors. Notably, EOL care selection, especially the use of complementary and alternative medicine (CAM), is associated with POD selection (death in PCU; OR=0.23, p=0.02). Conclusions: This study is, to the best of our knowledge, the first to unveil that EOL care selection is associated with POD in Japan. Certain factors such as gender, medical environment and EOL care selection might influence the POD. Patients who pursue aggressive anticancer therapies, such as CAM use, were possibly deprived of a chance of early reference to a PCU.